Comparative study of probiotic green and red cabbage juice – a nutraceutical approach - Ambawade, Mukund S; Shitole, Vaishnavi M; Tathawadkar, Srushti B; Abhyankar , Pragati S (Journal of Postharvest Technology, 2024)
The present study was conducted to compare the nutritional value of green cabbage juice with red cabbage juice. After fermentation, qualitative analysis of phytochemicals of fermented red cabbage juice and green cabbage juice, antioxidant potential, percentage of sugar, antagonistic activity, and shelf-life study were performed. After fermentation, qualitative analysis of phytochemicals of both the juices showed presence of various essential component and antimicrobial activity. Based on morphological and, biochemical characterization and on referring Bergey’s manual of determinative bacteriology, isolates from fermented cabbage juice were identified as Lactobacillus spp. Fermented red cabbage juice had greater ability to survive under gastrointestinal conditions than fermented green cabbage juice.